APLIKASI TEKNOLOGI CATALYTIC CONVERTER SISTEM SERABUT BAJA KARBON RENDAH PADA KENDARAAN BERMOTOR SEBAGAI PEREDUKSI POLUSI UDARA - Andi Sanata (Jurusan Teknik Mesin Fakultas Teknik Universitas Jember, 2016)
Technology of motor vehicles that are environmental friendly and fuel-efficient has been a demands in this era of energy crisis and global warming. The growth in number of motor vehicles which are very rapidly has raised the issue of air pollution that should be immediately resolved. Material utilization of iron (Fe) containing low carbon steel is often called low carbon as material for reducing pollution in this study applies principles of catalysation in motor vehicle exhaust gas pollutants with the material. The purpose of this research is generating a product of an architecture modification exhaust pollutants reducing motor vehicle by applying the technology of catalytic converter to reduce pollutant gases like CO and HC that are contained in the exhaust gas, as well as improving performance of the machine. The methods used to achieve these goals is the experimental method, which starts with design and creating of modification reducing exhaust gas as well as testing the effectiveness for emissions level and testing the poduct against the performance of the machine. The results of this research is the use of modification exhaust with application of catalytic converter technology with low carbon steel filler metals as catalysts in motor gasoline four steps can lower the levels of concentration of exhaust pollutants carbon monoxide (CO) and hydrocarbons (HC), increase torque, power, and lower fuel consumption than a standard exhaust conditions. Testing with a percentage of 75% volume of fibres low carbon steel has the best average results in the reduction of carbonmonoxide (CO) gases of 0.41% (lowered levels of CO 71.79% from the standard exhaust conditions) and hydrocarbons (HC) by 77.89 ppm (lowered levels of HC 61,25%), also can generate an increase in the average torque of 15.46% (with an average value of 4.23 Kg. m), an increase of the average effective power of 19.14% (with an average value of 11.76 HP), and decreasing in fuel consumption of 18.51% (with an average value of 1.48 Kg/hour) of the standard exhaust treatment conditions. Keywords: Catalytic Converter, Low Carbon Steel, Hydrocarbon, Carbonmonoxide